The HES framework - Scholz, Roland W.; Binder, Claudia R.; Lang, Daniel J. (Environmental Literacy in Science and Society, 2011)
Chapter overviewIn the spirit of cultivating environmental literacy we present the human–environment systems (HES) framework as a practical way to cope with the complexity of human–environment relationships. Its design and our suggestions for its use assume that most environmental problems are caused largely by human activities, a view that could be called the anthropocenic redefinition of the environment.Our unveiling of the HES framework describes how it is a structure–process template or methodological guide for research about HES. The HES framework highlights how the HES Postulates offer principles that foster a comprehensive analysis of HES.Next we describe how the HES framework offers principles for environmental research and transdisciplinary processes. After an initial phase of formulating a guiding question and defining system boundaries, a first step is to conduct an analysis of the environmental situation (as stated by the Environment-first Postulate P7), which is a typical subject of transdisciplinary processes.